Subjective and objective responses to two rugby sevens world series competitions - Fowler, P. M.; Murray, A.; Farooq, A.; Lumley, N.; Taylor, L. (The Journal of Strength and Conditioning Research, 2019)
The purpose was to examine the utility of subjective and objective measures of player preparedness, interpreted at both group level and individual level, during 2 consecutive competitions of the World Rugby Sevens Series (WRSS). Subjective (sleep, energy, and muscle soreness ratings) and objective (heart rate [HR] at rest [HRREST] and in response to submaximal exercise [HREX]) measures were obtained from 16 male rugby 7s players from 1 team for 3 consecutive days (D1-3) at home (HOME) and on arrival at 4 tournament (T1-4) locations (T1-New Zealand; T2-USA; T3-Hong Kong; and T4-Tokyo) across 2 WRSS competitions (2 tournaments per competition) separated by 1 month. At a group level, energy ratings were significantly lower in T2 and T4 compared with HOME, and on D1 T2 compared with D1 T1 (p = 0.05). Greatest variability in subjective ratings was observed during T1 and T3 at an individual level, particularly for sleep quality. Although at a group level HRREST and HREX significantly decreased in T1-4 compared with HOME (p = 0.05), there was only a ~50% agreement between the direction of change in HR indices at an individual level. Results from this study suggest that relocation between tournaments within WRSS competitions disrupts player preparedness measures to the largest degree. Hence, this period could be targeted by practitioners with appropriate recovery and/or sleep-promoting interventions or modulation of match-/training-load. Moreover, subjective rather than objective measures seem to be of greater use to inform player preparedness decision making, particularly at an individual level compared with a group level.